Histological Features of Scar Tissue Formation in Different Methods of Postoperative Wound Closure (Global Journal of Medical Research, 2023)
The aim is to study the features of histological and morphometric changes of skin scars in different variants of soft tissue wound closure Materials and methods 60 Wistar rats divided into 5 groups were operated on control group and 4 experimental ones interrupted loop sutures subcuticular suture adhesion with dermal glue Dermabond interconnection with high freaquency electrocoagulator HFEW Skin regeneration and scar formation were studied with histological and morphometric methods on 7th and 14th day Results On the day 7 after the closure of the wound defect the thickness of the perifocal epidermis was significantly increased by 1 5-2 4 times due to reepithelialization and the formation of granulation tissue No morphological differences in skin regeneration after interrupted and subcuticular sutures were found Application of Dermabond and HFEW caused progressive increase thickness of the epithelium
Keywords: scars; postoperative stage; morphological and morphometric methods; regeneration